A comparative study of intranasal desmopressin and intranasal ketamine for pain management in renal colic patients: a randomized double-blind clinical trial - Farhad Heydari; Reza Azizkhani; Saeed Majidinejad; Majid Zamani; Aref Norouzian (Clinical and Experimental Emergency Medicine, 2024)
Objective Urolithiasis is one of the most common urological diseases worldwide, usually presenting as renal colic that leads to severe pain that requires analgesic treatment. This study aimed to compare the efficacy of ketamine and desmopressin in the pain management of renal colic patients. Methods This double-blind, randomized clinical trial was conducted on renal colic patients referred to the emergency department from June 2021 to July 2022. Patients were randomly assigned to three groups. In the desmopressin group, patients were treated with intranasal desmopressin and intravenous ketorolac. The ketamine group was treated with intranasal ketamine and ketorolac. The control group received ketorolac and an intranasal placebo. Vital signs were evaluated at baseline and 60 minutes; and pain scores were assessed at baseline, 10, 30, and 60 minutes after treatment. Results Enrollment included 135 patients, the mean (standard deviation) age was 44.1±11.4 years, and 82 (60.7%) were men. The mean visual analog scale scores were significantly lower at 10, 30, and 60 minutes in the ketamine group (5.6±1.2, 3.0±1.1, and 0.9±0.9, respectively) compared to the control (8.2±1.1, 5.1±2.0, and 2.3±2.6, respectively) and desmopressin (6.7±1.8, 4.2±2.2, and 1.3±1.4, respectively) groups (P<0.05). Although patients in the desmopressin group had lower mean pain scores than the control group at 10, 30, and 60 minutes, this difference was only significant at 10 minutes after the intervention (P<0.05). No significant differences in vital signs were found at 60 minutes after treatment. Conclusion Ketamine showed more favorable analgesic effects in renal colic patients than desmopressin, although desmopressin showed efficacy in the first minutes posttreatment.